Transient in-cylinder gas flow characteristics of single cylinder port injection hydrogen fueled engine - Rahman, MM; Hamada, Khalaf I; Noor, M.M; Maleque, Md. Abdul; A. Bakar, Rosli; Kadirgama, K. (Science Publications, 2010)
Problem statement: The variation of the in-cylinder gas flow characteristics for single cylinder port injection hydrogen fueled internal combustion engine was investigated through transient state simulation. Approach: One dimensional gas dynamics was described the flow and heat transfer in the components of the engine model. Special attention is paid to selection and correction of heat transfer correlation which describe of in-cylinder heat transfer to coincide with the practical observations. The engine model was simulated with variable engine speed and Air Fuel Ratio (AFR). Engine speed varied from 2000-5000 rpm with increment equal to 1000 rpm, while AFR changed from stoichiometric to lean limit. Results: The acquired results showed that the maximum in-cylinder temperature and pressure obtained of 2753 K and 49.62 bar at 24°CA ATDC and 13°CA ATDC for AFR = 34.33 respectively, while the minimum in-cylinder temperature and pressure obtained of 1366 K and 29.14 bar at 18 deg CA of ATDC and 8 deg CA of ATDC for AFR = 171.65 respectively. The obtained results show that AFR has a crucial effect on characteristics variation during the power cycle whilst engine speed has minor effects. Conclusion: These results utilized for study the combustion process, fuel consumption, emission production and engine performance.